Comparative Analysis of Bacterial Diversity in Water Bodies in UTHM Pagoh Campus - Ibrahim, Muhammad Amri; Pa'ee, Furzani (Enhanced Knowledge in Sciences and Technology, 2025)
The study identifies the bacterial families in the water and compares the diversity between the residential college pond and the UTHM Wetland Conservation Research Station. As we can see, there is no prior information on bacterial diversity in Pagoh has been documented. So, the study aims to collect data on bacterial diversity in water bodies around the UTHM Pagoh Campus. Water quality measurements assessed levels based on the National Water Quality Standards and Water Quality Index.  The study identified bacterial families in the water bodies, comparing the diversity at both sites. Methods included water sample collection, water quality measurement, bacterial culture and isolation, morphological identification, gram staining, and bacterial identification. The water quality measurements show that the UTHM Wetland Conservation Research Station has lower measurements of pH, dissolved oxygen, and temperature while having higher measurements of conductivity and biochemical oxygen demand than the pond of the residential college which conclude the UTHM Wetland Conservation Research Station falls between Class IV and V, while the residential college pond falls between Class II and III. There are 3 samples which are Gram-positive cell walls and 3 samples Gram-negative cell walls. At the UTHM Wetland Conservation Research Station, there are 4 bacterial families; Neisseriaceae, Moraxellaceae, Micrococcaceae, and Planococcaceae. In contrast, the residential college pond revealed 3 bacterial families: Corynebacteriaceae, Pseudomonadaceae, and Staphylococcaceae. The differences in bacterial diversity are attributed to various factors, including species adaptations, site nutrient levels, organisms inhabiting the sites, and environmental conditions. For further study, the study can include DNA Quantification (spectrophotometer), preparation of PCR Cocktail, gel electrophoresis, Bioedit of sample sequences to get the sequence, NCBI blast for sample, and phylogenetic tree.